2014
DOI: 10.25269/jsel.v4i02.87
|View full text |Cite
|
Sign up to set email alerts
|

Pelet Reject Industri Kertas Sebagai Bahan Bakar Boiler

Abstract: Paper mill using recycle fiber as raw material produces reject containing fiber and plastic. The reject was identified by means of sorting. Reject pellet was prepared by drying, followed by shredding, and pellets molding. It was analyzed for its proximate composition (moisture, ash, volatile matter and fixed carbon). Calorific value, sulfur content, ash mineral content, and ash fusion temperatures were also tested. The results showed that reject consists of 50.75% fiber and 49.25% plastic of which is > 99% Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Solid/Reject waste component comprises fiber (paper fragments) up to 50.75% and plastic up to 49.25% (HDPE plastic-type > 99%) regarding the metal extracted from a small quantity of wire (Setiawan et al, 2014). The rising energy price in 2022 affected the cost of production or waste management using energy.…”
Section: Introductionmentioning
confidence: 99%
“…Solid/Reject waste component comprises fiber (paper fragments) up to 50.75% and plastic up to 49.25% (HDPE plastic-type > 99%) regarding the metal extracted from a small quantity of wire (Setiawan et al, 2014). The rising energy price in 2022 affected the cost of production or waste management using energy.…”
Section: Introductionmentioning
confidence: 99%
“…Plastics content on HR is usually relatively high. A study reported about 45% plastic content on HR without prior separation (Haynes, Malloch, Cuddy, & Nicodimos, 2009), while the contents were slightly higher (49,25%) after a metal separation treatment from HR (Setiawan, Purwati, Surachman, Bastari, & Hardiani, 2014). There are several types of plastic wastes that have thermoplastic characteristics and can be formed repeatedly with high temperature such as Polyethylene (PE) (Atuanya, Ibhadode, & Igboanugo, 2011;Faruk & Matuana, 2008;Li, Zheng, Pan, & Hartsough, 2009), Polypropylene (PP) (Ashori & Nourbakhsh, 2014;Septiari, Karyasa, & Kartowarsono, 2014), and Polystyrene (PS) (Mawardi, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of plastic in HR can be seen in Table 1. (Haynes et al, 2009) With metal separation (Setiawan et al, 2014) Fiber (paper, cardboard, etc. ) 21 Plastic waste is very difficult and will likely to take a long period of time to decompose in the natural environment.…”
Section: Introductionmentioning
confidence: 99%